2016
DOI: 10.1371/journal.pone.0155508
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA Analysis Suggests Negligible Impact of the Wari Empire Expansion in Peru’s Central Coast during the Middle Horizon

Abstract: The analysis of ancient human DNA from South America allows the exploration of pre-Columbian population history through time and to directly test hypotheses about cultural and demographic evolution. The Middle Horizon (650–1100 AD) represents a major transitional period in the Central Andes, which is associated with the development and expansion of ancient Andean empires such as Wari and Tiwanaku. These empires facilitated a series of interregional interactions and socio-political changes, which likely played … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Despite some controversy about definitions and chronology, archeologists identify a unique cultural process in Western South America, which include three temporal Horizons : Early, Middle, and Late, that corresponds to periods of cultural dispersion involving a wide geographic area 26 (Figure 2). In particular, the Middle and Late Horizons are associated with the expansions of the Wari (~1400 to 1000 YBP) and Inca (~524 to 466 YBP) states, respectively [27][28][29] . Isbell 28 has suggested that the Wari expansion has been associated with the spread of the Quechua language in the Central Andes and the Wari were pioneers in developing a road system in the Andes, called Wari ñam , which was later used as a base by We analyzed the distribution of IBD-segment lengths between individuals of different arid Andean populations, which is informative for the dynamics of past gene flow 3,30 , and observed a signature of gene flow in the interval 1400 to 1000 YBP, that is within the Wari expansion in the Middle Horizon ( Figure 2).…”
Section: Interactions Between Andean and Amazon Yunga Populations ?mentioning
confidence: 99%
“…Despite some controversy about definitions and chronology, archeologists identify a unique cultural process in Western South America, which include three temporal Horizons : Early, Middle, and Late, that corresponds to periods of cultural dispersion involving a wide geographic area 26 (Figure 2). In particular, the Middle and Late Horizons are associated with the expansions of the Wari (~1400 to 1000 YBP) and Inca (~524 to 466 YBP) states, respectively [27][28][29] . Isbell 28 has suggested that the Wari expansion has been associated with the spread of the Quechua language in the Central Andes and the Wari were pioneers in developing a road system in the Andes, called Wari ñam , which was later used as a base by We analyzed the distribution of IBD-segment lengths between individuals of different arid Andean populations, which is informative for the dynamics of past gene flow 3,30 , and observed a signature of gene flow in the interval 1400 to 1000 YBP, that is within the Wari expansion in the Middle Horizon ( Figure 2).…”
Section: Interactions Between Andean and Amazon Yunga Populations ?mentioning
confidence: 99%
“…In particular, this model of South American genetic structure typically overlooks the Pacific Coast, a key context for the early migration history of the continent 19 and the cradle of the earliest complex societies in South America, from 3000 BCE 20 . Recent studies have begun to investigate human variation on the Pacific coast through aDNA [21][22][23] and by sampling urban areas 11,24 , but to fill out this picture requires further, complementary genetic studies on living populations (especially from non-urban areas).…”
Section: Introductionmentioning
confidence: 99%
“…First, the haplotypes of autochthonous mtDNA lineages (A2, B2, C1 and D1) of the Panakas were compared with South American Genographic Database (with 2335 selected individuals from different populations), including published data (Álvarez-Iglesias et al 2007 ; Pauro et al 2013 ; Fehren-Schmitz et al 2015 ; Valverde et al 2016 ; Llamas et al 2016 ). To simplify the phylogenetic reconstruction, a group of closest haplotypes ( n = 193) was selected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, three individuals from ayllus Sucso (K6 and K7) and Avayni (K41) were included in this group. The ancient DNA samples were from the pre-Inka cultures of Lima and Chancay (ACAD10789 and ACAD11200 samples, respectively; Llamas et al 2016 ) and Ychsma (ACAD10713 and ACAD10720 samples; Valverde et al 2016 ). The second group of shared haplotypes included mostly Aymara- and Quechua-speaking individuals from the Altiplano region as well as K25 and K26 from the Pacarictampu District.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation